MANAJEMEN KONFLIK DALAM FILM MY NAME IS KHAN PERSPEKTIF KONSEP DAKWAH - Robby Aditya Putra (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2017)
History records a series of realities of conflict in the archipelago. The conflict in Sampit 2011, for example, happened due to misscommunication between ethnic Madura and Indigenous Dayak communities. SARA conflict in Maluku and Poso 1999-2001. Tragic and heartbreaking. Ideally, such conflicts need not be staged, even take victims. Given that no religion teaches it. But conflict is a necessity. Therefore, expertise in conflict management needs to be emphasized. This paper examines conflict management in the movie My Name is Khan (2010) viewed from the perspective of the three concept of da'wah (An-Nahl: 125). (1) Bil Hikmah (2) Al-Mauidzah al-hasanah (3) Al-Mujadalah. Thesis statement from this paper, My Name is Khan is a fairly mature Islamic film. With the jargon of My Name is Khan, and I am not a Terrorist, Director Karan Kapoor managed to present this slick film as a representation to end the conflict that includes Bil Hikmah, Al-Mauidzah al-hasanah and Mujadalah. But unfortunately, this film also contains about the excessive pluralis.